Engineering plants for a changing climate. - Joanna Clarke; Pamela C Ronald (PLoS Biology)
Climate change is affecting the types of plant varieties we can cultivate, as well as how and where we can do so. A new collection of articles explores the twin challenges of engineering plants for resilience to climate change and enhancing their carbon-capture potential.